2022
DOI: 10.1111/jnc.15562
|View full text |Cite
|
Sign up to set email alerts
|

Antagonists targeting eEF2 kinase rescue multiple aspects of pathophysiology in Alzheimer’s disease model mice

Abstract: It is imperative to develop novel therapeutic strategies for Alzheimer's disease (AD) and related dementia syndromes based on solid mechanistic studies. Maintenance of memory and synaptic plasticity relies on de novo protein synthesis, which is partially regulated by phosphorylation of eukaryotic elongation factor 2 (eEF2) via its kinase eEF2K. Abnormally increased eEF2 phosphorylation and impaired mRNA translation have been linked to AD. We recently reported that prenatal genetic suppression of eEF2K is ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
(76 reference statements)
1
7
0
Order By: Relevance
“…Both WT and eEF2K −/− mice exhibited normal learning during the training, indicated by marked day-to-day decreases in escape latency during the acquisition phase (Figures 2D,E). Consistent with previous studies (Zimmermann et al, 2020;Kasica et al, 2022), APP mice demonstrated longer escape latency, indicating a cognitive impairment (Figures 2D,E). Importantly, impaired learning observed in the APP mice was alleviated in the APP/eEF2K −/− mice, as demonstrated by improved day-to-day escape latency (Figures 2D,E).…”
Section: Knockout Of Eef2k Alleviates Long-term Recognition Memory De...supporting
confidence: 92%
See 4 more Smart Citations
“…Both WT and eEF2K −/− mice exhibited normal learning during the training, indicated by marked day-to-day decreases in escape latency during the acquisition phase (Figures 2D,E). Consistent with previous studies (Zimmermann et al, 2020;Kasica et al, 2022), APP mice demonstrated longer escape latency, indicating a cognitive impairment (Figures 2D,E). Importantly, impaired learning observed in the APP mice was alleviated in the APP/eEF2K −/− mice, as demonstrated by improved day-to-day escape latency (Figures 2D,E).…”
Section: Knockout Of Eef2k Alleviates Long-term Recognition Memory De...supporting
confidence: 92%
“…Moreover, substantial evidence indicates that eEF2K activity is not required for development or cell survival under physiological conditions. Transgenic mice with global knockout of eEF2K or wild-type mice treated with the chronic treatment of eEF2K inhibitors appear normal in numerous measurements of basic biological functions during development (Heise et al, 2017;Ma, 2021;Kasica et al, 2022). Thus, eEF2K could be a "safe" target, which is important for AD patients who usually need to take medicine continuously over a long period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations